NET-Mediated Pathogenesis of COVID-19: The Role of NETs in Hepatic Manifestations - Alkattan, Wael; Yaqinuddin, Ahmed; Shafqat, Areez; Kashir, Junaid (Journal of Health and Allied Sciences NU, 2022)
Some coronavirus disease-2019 (COVID-19) patients exhibit multi-organ failure, which often includes the liver. Indeed, liver disease appears to be an emerging feature of COVID-19 infections. However, the exact mechanism behind this remains unknown. Neutrophil extracellular traps (NETs) have increasingly been attributed as major contributors to various liver pathologies, including sepsis, ischemic-reperfusion (I/R) injury, and portal hypertension in the setting of chronic liver disease. Although vital in normal immunity, excessive NET formation can drive inflammation, particularly of the endothelium. Collectively, we propose that NETs observed to be elevated in severe COVID-19 infection play principal roles in liver injury in addition to acute lung injury. Herein, we discuss the potential mechanisms underlying COVID-induced liver injury including cytopathic effects from direct liver infection, systemic inflammatory response syndrome, and hypoxic injury, encompassing I/R injury and coagulopathy. Further research is required to further elucidate the role of NETs in COVID. This holds potential therapeutic significance, as inhibition of NETosis could alleviate the symptoms of acute respiratory distress syndrome and liver injury, as well as other organs.
Keywords: COVID-19; SARS-CoV2; NETs; liver disease; ACE2 receptor; multi-organ failure